Ubiquitin‐specific protease 24 negatively regulates abscisic acid signalling in Arabidopsis thaliana. (14th November 2015) - Zhao, Jinfeng; Zhou, Huapeng; Zhang, Ming; Gao, Yanan; Li, Long; Gao, Ying; Li, Ming; Yang, Yuhong; Guo, Yan; Li, Xueyong
Abstract: Abscisic acid (ABA) is an important plant hormone integrating environmental stress and plant growth. Protein ubiquitination and deubiquitination are reversible processes catalysed by E3 ubiquitin ligase and deubiquitinating enzyme, respectively. Lots of E3 ubiquitin ligase and transcriptional factors modified by ubiquitination were reported to modulate ABA signalling. However, no deubiquitinating enzyme has been identified that functions in ABA signalling until now. Here, we isolated an ABA overly sensitive mutant, ubp24, in which the gene encoding ubiquitin‐specific protease 24 (UBP24, At4g30890) was disrupted by a T‐DNA insertion. The ubp24 mutant was hypersensitive to ABA and salt stress in both post‐germinative growth and seedling growth. However, stomata closure in the ubp24 mutant was less sensitive to ABA, and the ubp24 mutant showed drought sensitivity. UBP24 possessed deubiquitinating enzyme activity, and the activity was essential for UBP24 function. Additionally, UBP24 formed homodimer in vivo . UBP24 was genetically upstream of ABI2, and the phosphatase activity of protein phosphatase 2C was decreased in the ubp24 mutant compared with the wild type in the presence of ABA. These results uncover an important regulatory role for the ubiquitin‐specific protease in response to ABA and salt stress in plant. Abstract : No deubiquitinating enzyme that functions in ABA signalling pathway has been identified until now. Here, we found that ubiquitin‐specific protease 24 (UBP24) possesses deubiquitinating enzyme activity and forms homodimer in vivo . UBP24 negatively regulates ABA signalling in post‐germinative and seedling growth probably by affecting the phosphatase activity of the protein phosphatase 2C.